Pengaruh Konseling Kelompok Teknik Cognitive Restructuring terhadap Self-Esteem Siswa - Rosidah, Lisa Lailatur; Mutakin, Fakhruddin; Nur Budiono, Arifin (Universitas PGRI Kanjuruhan Malang, 2024)
This study aims to examine the effect of group counseling using cognitive restructuring techniques on the self-esteem of 7th-grade students in class VII C at SMPN 02. The method employed in this research is quantitative, utilizing an experimental design, specifically the one-group pretest-posttest design. The population under study consists of 30 students from class VII C, with 6 students selected as the sample through purposive sampling. The instrument used is a self-esteem questionnaire for middle school students. The results showed that the t-value was greater than the t-table (34.5824 > 2.13185), thus the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. Therefore, the conclusion drawn from this study is that group counseling using cognitive restructuring techniques has an effect on students' self-esteem. It is hoped that this research will provide a positive contribution to the development of knowledge, particularly in the field of education, especially within the realm of guidance and counseling, in efforts to improve the quality of students, and serve as a reference for further research, thereby providing a foundation for future studies.